A Current Phase Decoupler for 5 G Smartphone Multiunit Frame Antenna - Hao-Miao Zhou; Chenghao Yuan; Di Wu; Yanqun Fang; Mingmin Zhu; Guoliang Yu; Yang Qiu (International Journal of Antennas and Propagation)
In this paper, based on the three-dimensional frame structure between the antenna unit and the ground, a decoupling method, the current phase decoupler method, is proposed for the 5 G smartphone multiunit frame antenna. Using this method in a dual-unit antenna, the additional current path reverses the phase of the coupled current flowing through the ground to the adjacent unit, while weakening the coupled current intensity and significantly suppressing the coupling between the units. The measured results show that the coupling is less than −28 dB, and the maximum efficiency is 85.53% without adding any lossy components. In an eight-unit smartphone antenna system, the coupling of adjacent units can also be reduced below −24.6 dB with a maximum efficiency of 82.17%. This method has significant advantages over the existing decoupling methods and can be used as the preferred decoupling scheme for the future 5 G smartphone multiunit frame antenna.